Robot controlled vacuum cleaner - Mohd Zain @ Ab. Razak, Rahimah (2005)
Hygiene is one of the most important factors in our life. Nobody wants to live in dirty places. Islam encouraged maintaining self- cleanliness and places where they live. Dust and dirt holds dust mite which can provoke asthma and allergy, especially in childhood. Regular use of vacuum cleaner will mop up those little dirt devils, and reduce the breeding cycle. However, in certain places such as mosque and prayer room which are enormously large, it takes quite a long time to clean the dust and dirt of the entire room. Thus, by building a robot controlled vacuum cleaner it can replace the conventional vacuum cleaner. This type of cleaner robot is able to clean these places without having to be manned. The robot controlled vacuum cleaner is built using microcontroller, motor driver circuit and sensors circuit. The microcontroller or Peripheral Interface Controller used in this project is PIC16F84A. The microcontroller coordinates the robot operations; it collects data from the sensors, runs a multi-tasking operation system, runs the consumption program and controls the stepper motor. The controller software for the system was developed using AutoCAD and MPLAB IDE software.